Determination the Level of Physical Activity and Eating Behaviors of University Students - Düz, Serkan; Aytekeli, Sümeyye Tuba (Asian Journal of Education and Training, 2020)
The aim of this study was to determine the relationship between level of physical activity and eating behaviors of university students. 270 students attending to Inonu University in 2018-2019 academic year and volunteering were included in the study. A short form of the International Physical Activity Questionnaire (IPAQ-SF) and the Dutch Eating Behavior Questionnaire (DEBQ) were administered to the participants along with the socio-demographic information form. Data were analyzed by IBM statistics (SPSS, version 25.0, Armonk, NY) windows package program and independent samples t test, Kruskal Wallis H test and Mann-Whitney U test were used with descriptive statistics. The findings were evaluated at 95% confidence interval and 5% significance level. While there was no statistically significant difference between eating habits, departments, classes, monthly income and place of residence of university students, there was a significant difference between BMI, adequate and balanced nutritional status and the reasons for skipping meals. Moreover, there was no significant relationship between eating behaviors and physical activity levels of university students, but men were more physically active than women were. As a conclusion, the possible effects of mood on eating behavior and physical activity should be determined in more detail by face-to-face interviews with students who have high scores from DEBQ questionnaire. Moreover, awareness can be enhanced by organizing trainings and information meetings in order to gain healthy eating habits along with physical activity.